Manajemen Integrasi Kurikulum pada MA Al-Mumtaz Gunungkidul Daerah Istimewa Yogyakarta - Muslim Fidia Atmaja; Na'imah Na'imah; Nur Saidah; Dwi Ratnasari (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2022)
The low quality of human resources and inadequate facilities in madrasas are new problems for educational institutions based on an integrated curriculum. If these conditions continue to be allowed, then the goals of Islamic education will experience obstacles. This qualitative research was conducted to analyze the integrated curriculum management, as well as the strengths and weaknesses of its implementation at MA Al-Mumtaz Gunungkidul Special Region of Yogyakarta. Based on reliable sources of document data and sources, through observation, documentation, and in-depth interviews, inductive analysis was carried out to find meaningful final findings of research results. The results show that at MA Al-Mumtaz, 3 integrated curricula have been implemented, namely, the National curriculum, the Islamic Boarding School curriculum, and the Entrepreneurship curriculum. Management principles are also implemented, starting from curriculum planning by the Pondok Pesantren component at the beginning of each new school year. The implementation of the curriculum is assigned to the coordinators of the education sub-section with its members to students. The implementation of the curriculum is based on the autonomy of the foundation, an integrated curriculum system, a curriculum modification system, and the primacy of affective assessment. Supervision is carried out at the beginning, middle, and end of the school year. Its strengths are the one-way command system, the creation of independent human resources, and the consistency of regulations at MA Al-Mumtaz. Meanwhile, its weaknesses are found in organizing educators and education personnel, as well as community acceptance.